Diversity of conformational states and changes within the EF-hand protein superfamily - Yap, Kyoko L.; Ames, James B.; Swindells, Mark B.; Ikura, Mitsuhiko (Proteins, structure, function, and bioinformatics, 1999)
The EF‐hand motif, which assumes a helix‐loop‐helix structure normally responsible for Ca2+ binding, is found in a large number of functionally diverse Ca2+ binding proteins collectively known as the EF‐hand protein superfamily. In many superfamily members, Ca2+ binding induces a conformational change in the EF‐hand motif, leading to the activation or inactivation of target proteins. In calmodulin and troponin C, this is described as a change from the closed conformational state in the absence of Ca2+ to the open conformational state in its presence. It is now clear from structures of other EF‐hand proteins that this “closed‐to‐open” conformational transition is not the sole model for EF‐hand protein structural response to Ca2+. More complex modes of conformational change are observed in EF‐hand proteins that interact with a covalently attached acyl group (e.g., recoverin) and in those that dimerize (e.g., S100B, calpain). In fact, EF‐hand proteins display a multitude of unique conformational states, together constituting a conformational continuum. Using a quantitative 3D approach termed vector geometry mapping (VGM), we discuss this tertiary structural diversity of EF‐hand proteins and its correlation with target recognition. Proteins 1999;37:499–507. ©1999 Wiley‐Liss, Inc.